Prognostic Value of Microvessel Density in Tumor and Peritumoral Area as Evaluated by CD31 Protein Expression and Argyrophilic Nucleolar Organizer Region Count in Endothelial Cells in Uterine Leiomyosarcoma. (15th July 2012) - Avdalyan, Ashot; Bobrov, Igor; Klimachev, Vladimir; Lazarev, Alexander
Abstract : The objective of this study was to investigate the prognostic value of microvessel density (MVD) in uterine leiomyosarcoma (LMS) and peritumoral area (PA) as evaluated by CD31 expression and argyrophilic nucleolar organizer region (AgNOR) count in endothelial cells. Tissue specimens from 66 patients with uterine LMS were examined. There were no significant differences in the mean MVD between tumor itself and the PA (P = 0.9 ); moreover, the MVD in the PA often exceeded that in the tumor. No correlation or significant differences were also found in the MVD between different grades of malignancy of LMS (r = 0.1 ; P = 0.07 ). The number of AgNORs in tumor endothelial cells was significantly higher in tumor vessels than in the peritumoral area (P < 0.005 ) and increased with the tumor grade. Analysis of the prognostic value of MVD in uterine LMS and PA showed that the density of tumor vessels was not an independent criterion, while the MVD in the PA affected 10-year survival to a significantly greater extent (χ 2 = 27.5 ; P = 0.0003 ). The number of AgNORs also had an important effect on survival of LMS patients: when the threshold of 11.6 granules was exceeded, prognosis was significantly more unfavorable than that prior to exceeding the threshold.